Serviço social, estado e desenvolvimento capitalista: (im)possibilidades neodesenvolvimentistas e projeto profissional - Paula, Renato Francisco dos Santos (2013)
The current thesis has as object of study the particularities of those developmentalist projects, present in the history of the evolution of Brazilian capitalism as well as its implications in Social Work and its professional projects. Under the lights of the political economy as a method, it departs from the assumption that the relationships established between State and the social classes are the hard core through which circulate the legitimacy and the social orientation of Social Work as a participating profession of the social and technical division of monopolist capitalism. That way, it recovers the evolution of the socio-historical debate on State not only as a category of critical analysis but also as an instrument that makes concrete the class interests through the collation to the Political Science canon as well as to the sociological and economic thoughts taken as universal. It also lends itself to the analysis of such fields of knowledge in its Brazilian version in order to induce to a totalizing perspective that does not abstain from listing the general and particular elements of the phenomenon in question. It regards the developmentalist projects as moments of synthesis of the evolutionary process of the national capitalism with special emphasis on the current cycle of accumulation in which there is a debate on the existence or not of a neo-developmentalist project whose deployments hold in check the reconfiguration of the private job market of Social Work as well as its ways of producing knowledge, analysis of the reality and ethical-political orientations, in its daily anti-systemic struggle